Psychological and organisational determinants of career success amongst women academics in Science, Technology, Engineering, Mathematics and Medicine (STEMM) - Lim, Hooi Shan (2020)
Science, Technology, Engineering, Mathematics and Medicine (STEMM) fields are commonly known to be male-dominated. The additional occupational challenges arising from the traditional roles of women in family and childcare are thereby thought to be compounded for women working in these fields. This thesis assessed the psychological and organisational factors impacting on the career success (research productivity, teaching performance, and career advancement) of women academics working in STEMM fields in Malaysia.